Engaging family members in maternal, infant and young child nutrition activities in low‐ and middle‐income countries: A systematic scoping review - Stephanie L. Martin; Juliet K. McCann; Emily Gascoigne; Diana Allotey; Dadirai Fundira; Katherine L. Dickin (Wiley, 2021)
Abstract The influence of fathers, grandmothers and other family members on maternal, infant and young child nutrition practices has been well documented for decades, yet many social and behavioural interventions continue to reach only mothers. While recent guidelines recommend involving fathers, grandmothers and other family members in maternal and child nutrition, we lack a comprehensive review of interventions that have engaged them. This scoping review aimed to address this gap by describing social and behavioural interventions to engage family members in maternal and child nutrition in low‐ and middle‐income countries. We systematically searched PubMed, Scopus, Web of Science, Global Health and CINAHL for peer‐reviewed studies meeting inclusion criteria. We screened 6,570 abstracts, evaluated 179 full‐text articles, and included 87 articles from 63 studies. Studies reported a broad range of approaches to engage fathers, grandmothers and other family members to support maternal nutrition (n = 6); breastfeeding (n = 32); complementary feeding (n = 6) and multiple maternal and child nutrition practices (n = 19). Interventions were facility and community based; included individual and group‐based interpersonal communication, community mobilization, mass media and mHealth; and reached mothers and family members together or separately. Most interventions were located within the health sector; rare exceptions included nutrition‐sensitive agriculture, social protection, early child development and community development interventions. Few interventions addressed gender norms, decision‐making, and family dynamics or described formative research or theories informing intervention design. These diverse studies can shed light on innovative programme approaches to increase family support for maternal and child nutrition.